Analisis Faktual Keterbatasan Pemanfaatan Sarana Dan Prasarana Penunjang Proses Belajar Mengajar Dilingkungan STT PLN - Rahma Farah Ningrum; Puji Catur Siswipraptini; Dian Hartanti (KILAT, 2016)
PLN Engineering of College (STT PLN) is a campus that has a big potential to continue to grow, especially in the Department of Information Engineering. Along with the continued increase in students, to impact the use of campus facilities and infrastructure for the learning process and also more dense lecture scheduling process. This study aims to find an effective solution to the limitations of the use of infrastructures means that the learning process can run smoothly. To avoid inconsistencies in the modeling, then the Focus Group Discussion (FGD) against the criteria, sub-criteria and strategic alternatives with respondents to determine the stage of making a valid model with significant elements that affect models. Results obtained from the questionnaire FGD are significant criteria, sub-criteria significant, and significant alternatives that make up the decision making process. Data processing respondents in this FGD, processed using statistical methods conchrant Q test. Having obtained the criteria, sub-criteria and strategic alternatives valid next step using Analytical Hierarchy Process (AHP) to the data processing using Expert Choice program in 2000.